Initial Public Offering : Issues and Procedures (Helping to Increase Capital Structure) - Singhal, R. K; Agarwal, Rahul (Journal of Commerce and Trade, 2008)
It is the initial public offer made by company to increase its capital structure. Companies provide opportunity to public to invest their money in their company. Companies effort to provide maximum profit to the public and keep their faith in the companies .The name and image play a vital roll in this sector Public prefer investing their money in reputed companies. Public invested about 6761 million in various IPO offered by various companies during the last three months .Near about 20 companies are going to offer their IPOs. The Indian economy is growing by leaps and bounds. you are a part of this phenomenal growth. The First Step initiative teaches you all the know-how about applying for the right IPOs. What’s more, it does so in an easy paperless manner.